Association of mean platelet volume with impaired myocardial reperfusion and short-term mortality in patients with ST-segment elevation myocardial infarction undergoing primary percutaneous coronary intervention. Issue 1 (January 2016) - Lai, Hong-Mei; Chen, Qing-Jie; Yang, Yi-Ning; Ma, Yi-Tong; Li, Xiao-Mei; Xu, Rui; Zhai, Hui; Liu, Fen; Chen, Bang-Dang; Zhao, Qian
Abstract : Impaired myocardial reperfusion, defined angiographically by myocardial blush grade (MBG) 0 or 1, is associated with adverse clinical outcomes in patients with ST-segment elevation myocardial infarction (STEMI). The aim of this study was to investigate the impact of admission mean platelet volume (MPV) on the myocardial reperfusion and 30-day all-cause mortality in patients with STEMI with successful epicardial reperfusion after primary percutaneous coronary intervention (PCI). A total of 453 patients with STEMI who underwent primary PCI within 12 h of symptoms onset and achieved thrombolysis in myocardial infarction (TIMI) 3 flow at infarct-related artery after PCI were enrolled and divided into two groups based on postinterventional MBG: those with MBG 2/3 and those with MBG 0/1. Admission MPV was measured before coronary angiography. The primary endpoint was all-cause mortality at 30 days. MPV was significantly higher in patients with MBG 0/1 than in patients with MBG 2/3 (10.38 ± 0.98 vs. 9.59 ± 0.73, P  < 0.001). The cumulative 30-day all-cause mortality rate was significantly higher in the groups with high MPV and MBG 0/1 (6.8 vs. 1.5%, P   =  0.005, 7.6 vs. 1.9%, P   =  0.006, respectively). Multivariate logistic regression analysis demonstrated MPV was independently associated with postinterventional impaired myocardial reperfusion (odds ratio 2.684, 95% confidence interval 2.010–3.585, P  < 0.001) and 30-day all-cause mortality (hazard ratio 1.763, 95% confidence interval 1.009–3.079, P  = 0.046). Increased MPV on admission is an independent predictor of impaired myocardial reperfusion and short-term mortality in patients with STEMI with successful epicardial reperfusion after primary PCI. Admission MPV may be additive to conventional risk factors in patients with STEMI undergoing PCI.